Generation Expansion Planning Considering the Output and Flexibility Requirement of Renewable Energy: The Case of Jiangsu Province - Lv, Tao; Yang, Qi; Deng, Xu; Xu, Jie; Gao, Jian (Frontiers in Energy Research, 2020)
This study presents a generation expansion planning by incorporating the impacts of renewable energy on the generation mix. The wind–solar power output and its flexibility requirement are integrated into an optimization model to provide the realistic representation of wind and solar energy resources. The model is then used for the power system optimization planning of Jiangsu Province. A comparison of power demand, electricity price subsidies, and carbon emission intensity scenarios reveals the power planning scheme and optimization path for power system integrating increasing renewable energy. The results suggest that the installed capacity of renewable energy will increase from 21.6 to 133.2 GW in the baseline scenario during the planning period, with its share ranging from 17.9 to 53.7%. Solar photovoltaic power is expected to contribute 72% of renewable capacity and 39% of total capacity by 2050. The impact of electricity price subsidies on solar PV generation expansion is particularly significant. Additionally, the flexibility requirement of power systems can basically be satisfied with the available generation technologies; however, it would become severe if the flexibility requirement grows faster than the flexible generation.